Plasshensyn i tospråklige ordbøker - Haraldsson, Helgi (Nordiske Studier i Leksikografi, 1995)
The maximum of information in a minimum of space is a natura! goal in a bilingual dictionary such as H. Haraldsson’s Russian-Icelandic dictionary (to appear in early 1996). Gradually, various methods have been developed to reach this goal, some of which can be seen in V. Berkov’s Russian-Norwegian dictionary of 1987 (rev. ed. 1994). In this paper, the author describes some of the methods used in the dictionary to save space and condense information. He shows that among other things, precious space can be sa ved by means of a careful analysis of the semantics, distribution and stylistic value of synomyms.